Analisis Meme Analysis of Political Memes in Social Media: Meme Politik - Shinta Noviana Lubis Shinta; Nur Hafizah; Asrul Siregar; Siti Ayu Nurhidayati (Rahis Cendekia Indonesia, 2024)
Internet use in Indonesia is very active with the existence of social media. This gave birth to a new phenomenon among internet users with creativity in making memes. The memes that are currently developing are in the form of images and videos. This meme is defined as an idea, behavior, style, entertainment that spreads from one person to another. Memes on social media have become a vehicle for entertainment because they are funny and contain parodies. However, memes also often cause problems where someone thinks that everything can be used as a joke in the form of a meme and the aim is to corner certain parties. Moreover, if a meme contains elements of a political meme, many people like to edit the meme as a daily joke. The aim of this research is to get an overview of the semiotic elements in political memes circulating on social media. This research method is semiotic analysis using Charles Peirce's semiotic approach (signs, objects and interpreters). The research results concluded that there is a close relationship between signs, objects and interpreters. Meme signs (images) created by netizens responding to feuds between political memes. The object (meaning) generally contains scorn, sarcasm and netizens' dislike for Lulung and is packaged in the form of satire (humor). Meanwhile, the interpretation or attitudes (thoughts) of meme creators and netizens tend to be the same. Where netizens generally accept and agree with the contents of this meme and support each other.